Forcing Subsets of Connected Co-Independent Hop Domination in the Join and Corona of Graphs (European Journal of Pure and Applied Mathematics, 2022)
This study deals with the forcing subsets of a minimum connected co-independent hop dominating sets in graphs. Bounds or exact values of the forcing connected co-independent hop domination numbers of graphs resulting from some binary operations such asjoin and corona of graphs are determined.Some main results generated in this study include characterization of the minimum connected co-independent hop dominating sets, characterization of the forcing subsets for these types of sets, and bounds or exact values of the forcing connected co-independent hop domination numbers of the join and corona of graphs.
Keywords: Forcing subsets; connected co-independent hop domination; strictly co-independent set